If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) + 5(x + -2) = 15x Reorder the terms: 3(-2 + x) + 5(x + -2) = 15x (-2 * 3 + x * 3) + 5(x + -2) = 15x (-6 + 3x) + 5(x + -2) = 15x Reorder the terms: -6 + 3x + 5(-2 + x) = 15x -6 + 3x + (-2 * 5 + x * 5) = 15x -6 + 3x + (-10 + 5x) = 15x Reorder the terms: -6 + -10 + 3x + 5x = 15x Combine like terms: -6 + -10 = -16 -16 + 3x + 5x = 15x Combine like terms: 3x + 5x = 8x -16 + 8x = 15x Solving -16 + 8x = 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -16 + 8x + -15x = 15x + -15x Combine like terms: 8x + -15x = -7x -16 + -7x = 15x + -15x Combine like terms: 15x + -15x = 0 -16 + -7x = 0 Add '16' to each side of the equation. -16 + 16 + -7x = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -7x = 0 + 16 -7x = 0 + 16 Combine like terms: 0 + 16 = 16 -7x = 16 Divide each side by '-7'. x = -2.285714286 Simplifying x = -2.285714286
| 3(5x+2)=2(3-6) | | m+17=34 | | 10x-10+2=-26 | | 3x+53=6x-35 | | 4/7x=11/x-3 | | m+17=134 | | 5x-48=-x | | -10y-3y-7=-12 | | 43x=8-4y | | 2c+22=7c-10 | | 3(x+4)+8=-10 | | 2(x-5)-4-5x+1=0 | | x=.5(3x-13) | | 2x+y-76=0 | | x=.5(2x-10-3) | | 291+x=360 | | v+2.59=4.69 | | 2y-2+4y-32+y+8=360 | | x-61=12.5 | | 12Y+17=161 | | X^2-18x+81=2001 | | 27.48+x=3.29x | | -5x-6+4x=12 | | 3x-6(-5x+17)=162 | | -3y-1+2y=-1 | | (4x-40)/2=(2x-90)x4 | | (4x-40)/2=(2x-90)4 | | -1/8(8y-72) | | (4x-40)/2=(2x-90)*4 | | v-2.14=4.4 | | w*8+4=13 | | Y=x^2+9x-112 |